2017
DOI: 10.1088/1741-4326/aa6dca
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear simulation of ELM dynamics in the presence of resonant magnetic perturbations

Abstract: We report on nonlinear simulation studies on the dynamical behaviour of ELMs under the influence of resonant magnetic perturbations (RMPs) using a two-fluid initial value electromagnetic nonlinear global code (CUTIE). To simulate ELMs we introduce a particle source in the confinement region and a particle sink in the edge region. To study ELM control using RMPs we have applied an n = 2 static external magnetic perturbation at the edge and made detailed parametric studies under varying conditions for the machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 23 publications
3
31
0
Order By: Relevance
“…For n=2 and 3, the system continues to remain in an ELM mitigated state, whereas for n=4, the system goes back to the initial ELMy state. This is demonstrated by presenting the waveforms and power spectra of the plasma turbulence and ELMs; and (iv) there are significant RMP effects on the profiles and confinement, as already found in [12] for the case of n=2.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…For n=2 and 3, the system continues to remain in an ELM mitigated state, whereas for n=4, the system goes back to the initial ELMy state. This is demonstrated by presenting the waveforms and power spectra of the plasma turbulence and ELMs; and (iv) there are significant RMP effects on the profiles and confinement, as already found in [12] for the case of n=2.…”
Section: Introductionsupporting
confidence: 58%
“…We next turn to the question of how the transitions in the turbulence (both waveform amplitudes and spectral characteristics) affect the global properties such as ‘Density pump out’ and βfalse(normal%false)) post-transition. In [12], the effects of switching on an RMP (n=2,K=4) were considered on β,τnormalE,τp with the density feedback: it was shown that while, after an initial transient, β, τnormalE increase, the particle confinement is slightly degraded relative to the no RMP case, in spite of the feedback control of the plasma particle number, Nnormaltotfalse(tfalse); this occurs under the assumed conditions of the switch-on of a constant RMP field. The experiments show that both particle and energy confinement can be degraded after an RMP is used, especially when its strength is increased in time.…”
Section: Results Of Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are further found to be sensitive to the pellet size. A comparison with our past results on RMP induced mitigation of ELMs [16] shows that pellets are more effective in raising the plasma beta and improving the energy confinement times of the system. Such an improvement of the energy confinement with the introduction of pellets has been observed in experiments as on ASDEX [23].…”
Section: Summary and Discussionmentioning
confidence: 73%
“…In this work, we report on nonlinear simulation studies using CUTIE that are aimed at exploring the dynamical behavior of ELMs under the influence of repetitive injection of pellets. We also compare and contrast the effects of pellets and RMPs [16] on ELMs.…”
Section: Introductionmentioning
confidence: 99%